Absorptive Hydrogen Scavenging for Enhanced Aromatics Yield During Non‐oxidative Methane Dehydroaromatization on Mo/H‐ZSM‐5 Catalysts. Issue 47 (30th October 2018) - Kumar, Anurag; Song, Kepeng; Liu, Lingmei; Han, Yu; Bhan, Aditya
Abstract: Addition of Zr metal particles to MoC x /ZSM‐5 in interpellet mixtures (2:1 weight ratio) resulted in maximum single‐pass methane conversion of 27 % for dehydroaromatization at 973 K (in significant excess of the equilibrium prescribed circa 10 % conversion at these conditions) and a concurrent 1.4–5.6‐fold increase in aromatic product yields due to circumvention of thermodynamic equilibrium limitations by absorptive H2 removal by Zr while retaining cumulative aromatic product selectivity. The absorptive function of the polyfunctional catalyst formulation can be regenerated by thermal treatment in He flow at 973 K, yielding above‐equilibrium methane conversion in successive regeneration cycles. H2 uptake experiments demonstrate formation of bulk ZrH1.75 on hydrogen absorption by Zr at 973 K. Cooperation between absorption and catalytic centers distinct in location and function enables circumvention of persistent thermodynamic challenges in non‐oxidative methane dehydrogenation. Abstract : Addition of Zr metal particles to MoC x /ZSM‐5 in interpellet mixtures resulted in maximum single‐pass methane conversion of 27 % for dehydroaromatization at 973 K (in significant excess of the equilibrium prescribed circa 10 % conversion at these conditions) and a concurrent 1.4–5.6‐fold increase in aromatic product yields.